Producción musical del tema Burning Fyah de la banda Bongo Station - Semanate Trávez, Xavier Guillermo (2017)
The musical production is a set of techniques and creative processes that allow the development of a raised project. The current project aims to produce the song “Burning Fyah” from the band Bongo Station, using techniques and tools learned in the course of the race, to obtain the second record material of this group. As a first step is taken to research that will allow to obtain some knowledge and experience about the musical genre, its characteristic sonority, musicality and its proper instrumentation. There are three stages of production where each one of them is worked with one objective mainly. In the pre-production, certain details of the theme are defined in agreement with the band as: composition of musical arrangements, rehearsals, schedules, meetings, among other things. Subsequently, the stage of production is where the recording and realization of the visual art of the disc implies. Finally, there is the post-production stage, where a characteristic sonority is defined for the product using different mixing techniques, previously with editing to correct the recorded tracks and also the design of the visual art is finished. When concluding with the musical production and obtaining a product with the appropriate technical and musical characteristics, it fulfills the mission that the subject can compete within the Ecuadorian musical industry; Besides generating a professional growth of the musical producer within the fusion of a new genre conformed between Rap and Reggae.